Cytomegalovirus infection in high‐risk kidney transplant recipients receiving thymoglobulin induction—a single‐center experience. Issue 9 (1st August 2016) - Puttarajappa, Chethan; Bhattarai, Manoj; Mour, Girish; Shen, Chengli; Sood, Puneet; Mehta, Rajil; Shah, Nirav; Tevar, Amit D.; Humar, Abhinav; Wu, Christine; Hariharan, Sundaram
Abstract: Background: The burden of cytomegalovirus infection in CMV high‐risk (donor positive to recipient negative) kidney transplant recipients getting thymoglobulin induction and six months of valganciclovir is not well characterized. Additionally, the role of post‐prophylaxis surveillance remains unclear. Methods: One‐year observational study of forty‐eight high‐risk CMV kidney transplant recipients transplanted under thymoglobulin between January 2013 and July 2014. All received valganciclovir for six months, followed by monthly CMV PCR for three months. Results: CMV infection defined as viremia with or without symptoms occurred in 40% (19/48). Of these, 47% (9/19) occurred during prophylaxis, 32% (6/19) during surveillance and 21% (4/19) during post‐surveillance period (9–12 months). Among breakthrough infections, suboptimal valganciclovir dosing was present in 55% (5/9). With routine surveillance, there was a trend toward lower CMV‐related hospitalization (17% vs 56% and 75% during prophylaxis and post‐surveillance, respectively [ P =.23]) and lower mean peak viral loads (19 432 copies/mL vs 97 925 copies/mL and 536 021 copies/mL during prophylaxis and post‐surveillance, respectively [ P =.07]). Conclusion: CMV infection remains a significant problem with thymoglobulin induction despite six months of valganciclovir. Suboptimal valganciclovir dosing was common among breakthrough infections. Monthly surveillance post‐prophylaxis appears to detect early CMV infection with lower degree of viremias requiring fewer hospitalizations.